IMPLEMENTASI MODEL PEMBELAJARAN ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, SATISFACTION) UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA SISWA - Wiyanoto, Yudi; Partono, Partono; Riswanto, Riswanto (Universitas Muhammadiyah Metro, 2022)
Abstract: The results of the presurvey in class X MIA 2 of SMAN 1 Trimurjo, that there are 71% of students with the ability to understand the concept are in low and very low criteria. Therefore, it is necessary to improve the learning process by using the ARIAS learning model. This ARIAS learning model includes the stages of Assurance, Relevance, Interest, Assassment and Satisfaction. This research is Classroom Action Research (CAR) which cycles with the planning, implementation, observation and reflection stages. The research subjects were students of class X MIA 2 of SMAN 1 Trimurjo with a total of 35 students. Data collection instruments use observation sheets and test questions. The results showed that, the application of the ARIAS learning model was able to improve the achievement of indicators of understanding concepts including translating, explaining, and expanding. the percentage of students who are in the criteria is very good and good reaching 83%, with an increase of 54% from the initial data of prasurveyKeywords: ARIAS learning model and conceptual understanding